2022
DOI: 10.3390/app12104804
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Techniques for Business Recommender Systems

Abstract: Besides the typical applications of recommender systems in B2C scenarios such as movie or shopping platforms, there is a rising interest in transforming the human-driven advice provided, e.g., in consultancy via the use of recommender systems. We explore the special characteristics of such knowledge-based B2B services and propose a process that allows incorporating recommender systems into them. We suggest and compare several recommender techniques that allow incorporating the necessary contextual knowledge (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As for hybrid recommender systems, they combine the two approaches: use of evaluations and information given by the user [28][29][30][31][32].…”
Section: Recommender Systems Methodsmentioning
confidence: 99%
“…As for hybrid recommender systems, they combine the two approaches: use of evaluations and information given by the user [28][29][30][31][32].…”
Section: Recommender Systems Methodsmentioning
confidence: 99%
“…Wang and Su (2015) in their architecture iGeoTutor assisted students in mastering geometry theorems by implementing search strategies (e.g., DFS) from partially complete proofs. Pande et al (2021) aims to improve individual and self-regulated learning in group assignments through a conversational system built using NLU and dialogue management systems that prompts the students to reflect on lessons learnt while directing them to partial solutions.…”
Section: Reactive Engagement Of Ai For Education Tutoring Aidsmentioning
confidence: 99%
“…Similarly, Niwash et al (2022) found that BI has a positive effect on competitive advantage and business performance. BI tools can track, analyse, and display key performance indicators (KPI) metrics to monitor the health of a business (Pande et al, 2022). Recent innovative technologies, such as artificial intelligence (AI), can support businesses through disruption (Naz et al, 2022).…”
Section: Business Intelligence and Construction Companiesmentioning
confidence: 99%